2022
DOI: 10.1021/acs.cgd.2c00906
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of the BiySb2–yTe3–xSex 3D Topological Insulator: Physical Vapor Deposition and Molecular Beam Epitaxy

Abstract: Bi y Sb2–y Te3–x Se x (BSTS) topological insulator (TI) thin films were grown by physical vapor deposition (PVD) and molecular-beam epitaxy (MBE) and compared by growth parameters, substrate selection, preparation, and resulting film properties. For the MBE-grown BSTS on Si(111)-(7 × 7), preliminary deposition of the Bi2Te3 buffer layer at the Te-rich growth condition was found to improve the film structural properties. Using a BSTS crystal as the main source for deposition allows us to significantly decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A detailed description of the film growth is reported elsewhere. 15 In the present study, SiC/graphene composites used for the growth of BSTS thin films were deposited on semi-insulating 6H-SiC substrates by thermal decomposition. 20,21 Atomic force microscopy in scanning mode was employed for the investigation of topography and roughness of the samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the film growth is reported elsewhere. 15 In the present study, SiC/graphene composites used for the growth of BSTS thin films were deposited on semi-insulating 6H-SiC substrates by thermal decomposition. 20,21 Atomic force microscopy in scanning mode was employed for the investigation of topography and roughness of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…12 Stepina et al observed a higher degree of bulk insulation in BSTS compounds. 15 In this work, 15 the choice of substrate for the growth of BSTS films also played an important role in their bulk insulating properties, electronic properties, and transport. Weak antilocalization was observed for the BSTS films grown on the Si/SiO 2 /graphene substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation